Industrial training report: Research Industry Linkages & Alumni Universiti Teknologi MARA Kelantan (Machang Campus) / Muhammad Izzat Abdul Rahman - Abdul Rahman, Muhammad Izzat (Perpustakaan Tengku Anis, 2018)
This industrial training report consists of 4 chapters and they are introduction, organization of information, industrial training activities and conclusion. Chapter 1 consist of background of the organization, chapter 2 consist of departmental structure and function. While chapter 3 consists of training activities and special project and the last chapter is chapter 4 which has the conclusion of the report. In order to complete study, trainee needs to undergo 5 months of practical training in industry starting/ram 1 August 2018 until 31 December 2018. Research Department under UiTM that has been selected by trainee is Research Industrial Linkages and Alumni (P JIA). There are Unit of Research Management & Innovation (URMI), Industrial, Community and Alumni Network (!CAN), Malaysian Academy of SME & Entrepreneurship Development (MASMED), Poverty Eradication Research Centre (PERC) and Creative Hub and Media (CMT). Every unit has their own specialty, with interesting task and function. During five months of training, trainee got opportunity to learn office management in UiTM. Training schedule has been prepared by the Executive Officer in P JI for the trainee to learn important task. Besides that, student also learn to improve communication skills, learn to be more discipline and punctuality. Last but not least, the knowledge, skills and experience gain during the practical training is the best method in order to prepare student to expose to the real working environment and also to be a good and better person in future.